Preemption a knife that cuts both ways - Dershowitz, Alan M. 1938- (W. W. Norton & Company, 2006)
Identifies the benefits and consequences of the nation's paradigm shift toward more preventive and proactive approaches to conflict, arguing that the seeds of such a shift were planted prior to the events of September 11.
Includes bibliographical references and index
Keywords: Attaque préventive (Science militaire); Criminaliteit; Juridische aspecten; Politieke aspecten; Preventie; Préemption; Terrorisme; Violence - Prévention; Zelfverdediging; Kriminalität; Politik; Terrorismus; Violence -- Prevention; Preemptive attack (Military science); Pre-emption; Präventivkrieg